KETERSEDIAAN DAN KEBUTUHAN AIR DI PROVINSI JAWA TENGAH DAN JAWA TIMUR - Purnama, dkk, Setyawan (Jurnal Rekayasa Lingkungan)
There are two objectives of this research. First, to calculate water available and water need in the research area and second, to analysis the water balance. Water available cover rivers water and springs water, whereas water need cover domestic usage, industrial usage, rivers protect, cattle, fi shery and irrigation. As a result, show that the biggest water available in Central Java is in Serayu River Basin namely 8615.33 million m3/year, whereas the smallest is in Juana River Basin namely 88.39 million m3/year. In East Java, the biggest water available is in Downstream Bengawan Solo River Basin namely 26149.38 million m3/year, whereas the smallest is in Luminu Penguluran River Basin namely 45.26 million m3/year. Base on the water balance, the water balance of both province are also variatifl y. In Central Java, Serang-Lusi, Juana and Citanduy River Basin get water defi cit along years, whereas in East Java, it is just Luminu Penguluran River Basin that get defi cit along years. According the water surplus, Serayu River Basin in Central Java and Downstream Bengawan Solo River Basin in East Java get water surplus along years.Key words : water available, water need, water balance